2008
DOI: 10.1159/000161077
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Push/Pull Hemodialysis in a Canine Renal Failure Model

Abstract: A new dialysis modality was devised to increase convective mass transfer. Blood and dialysate are circulated by a pulsatile pump, but with pulsatile flow patterns that are 180° out of phase, which causes blood-to-dialysate pressure gradients to oscillate between positive and negative. In the present study, hemodialytic performance of the devised modality was investigated using a canine renal failure model. Membrane hydraulic permeabilities (Kuf) and fiber bundle volumes (FBV) were measured after eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Observed post-treatment membrane permeabilities were better maintained during PPPHD than during CHD, presumably due to the reduced membrane fouling resulting from the repetitive backfiltration [44].…”
Section: One-way Valvementioning
confidence: 99%
See 1 more Smart Citation
“…Observed post-treatment membrane permeabilities were better maintained during PPPHD than during CHD, presumably due to the reduced membrane fouling resulting from the repetitive backfiltration [44].…”
Section: One-way Valvementioning
confidence: 99%
“…Pulse push/pull hemodialysis combined with dual dialysate pulsation Pulsatile circulation of blood and dialysate offers a simple and efficient strategy for the repetitive cycle of filtration and backfiltration [43][44][45]. However, blood pulsation during extracorporeal renal replacement treatment is potentially problematic.…”
Section: One-way Valvementioning
confidence: 99%
“…As dog is the large animal model of choice for evaluation of renal cell therapies [20], we examined expression of EPO protein in canine kidney sourced adipose stromal cells and primary renal cells using IEF gels. Figure 10 demonstrates that canine KiSAS cells sourced from either major calyx adipose (lane 3) or renal pedicle adipose (lane 4) express EPO protein at levels comparable to that observed from canine primary renal cells (lanes 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…The hemodialytic efficiencies of the revised PP unit have been demonstrated in vitro and also in vivo, and these studies have shown that the devised PP unit substantially improves the clearances of uremic marker molecules, particularly for mid-sized molecules. 73,77 Pressure profiles also showed obvious oscillations of TMPs throughout treatment, and their magnitudes were significantly larger than those observed in HD mode. More recently, due to concerns with the pulsatile circulation of blood, particularly in terms of blood supply and vascular access, this unit has been further improved by eliminating blood pulsation, but retaining the recurrent forward and backward filtration procedures, which was achieved by integrating a dual pulsatile device in the dialysate stream.…”
Section: Push/pull Techniquesmentioning
confidence: 92%